A Clinical Protocol to Increase Chewing and Assess Mastication in Children With Feeding Disorders. (September 2014) - Volkert, Valerie M.; Peterson, Kathryn M.; Zeleny, Jason R.; Piazza, Cathleen C.
Children with feeding disorders often cannot or do not chew when presented with table food. Children with chewing deficits also often swallow the bite before masticating it appropriately, which we will refer to as early swallowing. In the current study, we evaluated a clinical protocol to increase chews per bite, assess mastication, and eliminate early swallowing with three children with feeding disorders. The current study adds to a small body of literature on chewing and mastication of children with feeding disorders. Suggestions for future research are also discussed.